2014
DOI: 10.11646/phytotaxa.167.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Tragopogon anatolicus (Asteraceae), a new species from east Turkey 

Abstract: The new species, Tragopogon anatolicus A.Duran, B.Doğan & Coşkunç. sp. nov. (Asteraceae) is described and illustrated from Cilo Mt. (Hakkari), south-east Anatolia, Turkey. Tragopogon anatolicus is a local endemic, most similar to T. buphthalmoides (DC.) Boiss. Diagnostic morphological characters of these two closely related taxa are discussed. A phylogenetic analysis based on nrDNA ITS sequence data indicated that T. buphthalmoides is the sister species of the new taxon. Ecology, biogeography and conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…m). Micro‐projections were also observed in T. orientalis L. by Das and Mukherjee () and in T. anatolicus by Dogan et al (). Although achenes of the T. vanensis and T. reticulatus are similar in gross morphology, the beak apex is globular with a hairy annulus in T. vanensis (Fig.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…m). Micro‐projections were also observed in T. orientalis L. by Das and Mukherjee () and in T. anatolicus by Dogan et al (). Although achenes of the T. vanensis and T. reticulatus are similar in gross morphology, the beak apex is globular with a hairy annulus in T. vanensis (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…), as reported by Wodehouse () and Blackmore (). Suboblate (İnceoğlu and Karamustafa , Gültepe et al ) and oblate‐spheroidal (Blackmore , Dogan et al ) have previously been reported in Tragopogon . As seen in Table , the suboblate and oblate‐spheroidal pollen grains identified in the present study were consistent with previous findings.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For the phylogenetic reconstruction, seventeen accessions belonging to Tragopogon and five accessions belonging to Scorzonera L., Lactuca L., Gerepogon L., Hieracium L. and Scolymus L. were used. Sequence data for twelve accessions were obtained from Dogan et al () and GenBank ( Lactuca serriola L. AJ633331, Scolymus hispanicus L. AJ633471), and sequence data for ten accessions were newly prepared for this study (Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…In Turkey, according to Coşkunçelebi and Gültepe (), Tragopogon is represented by 21 species excluding doubtfully recorded taxa and recently described taxa from southeast Turkey (Dogan et al ).…”
mentioning
confidence: 99%